The effect of an educational video game on high school students’ motivation, self-efficacy and knowledge in a History course - Zapata, Claudia (2024)
The purpose of this study was to explore the effects of an educational video game on high school students’ motivation, self-efficacy and knowledge. The game tells the story of Mariano Melgar, a Peruvian thinker, patriot and hero. The authors used a quasi-experimental design and conducted pre- and post-tests to estimate the effect of the video game. The sample consisted of 67 students from two schools in Lima. The students were randomly assigned to one of two conditions: playing a video game or watching a documentary. Results show that playing the video game was more effective in increasing students’ knowledge, whereas watching a documentary increased demotivation and decreased self-efficacy through vicarious experience. In view of this, it is important to explore further video games’ usefulness as educational materials.